Global Growth and Financial Spillovers and the South African Macro-economy - Ncube, Mthuli; Gumata, Nombulelo; Ndou, Eliphas; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book offers new quantitative insights into how South African economy reacts to external economic shocks. The analysis includes focusing on economic growth and financial spill over, effects of capital inflows, contrasting the stock market price returns and volatility on economic growth and determining the effects of financial stress.
Keywords: Knowledge management; Investment banking; Securities; Macroeconomics; International economics; Economics; Macroeconomics/Monetary Economics//Financial Economics; International Economics; Knowledge Management; Investments and Securities; Electronic books